2002
DOI: 10.2172/793401
|View full text |Cite
|
Sign up to set email alerts
|

Iterative Solvers and Preconditioners for Fully-Coupled Finite Element Formulations of Incompressible Fluid Mechanics and Related Transport Problems

Abstract: Finite element discretization of fully-coupled, incompressible flow problems with the classic mixed velocity-pressure interpolation produces matrix systems that render the best and most robust iterative solvers and preconditioners ineffective. The indefinite nature of the discretized continuity equation is the root cause and is one reason for the advancement of pressure penalty formulations, least-squares pressure stabilization techniques, and pressure projection methods. These alternatives have served as admi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
7
0

Year Published

2004
2004
2013
2013

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 47 publications
0
7
0
Order By: Relevance
“…In addition, some researchers have found that stabilized element formulations can lead to improved performance of iterative solvers, see e.g. [24].…”
Section: Numerical Resultsmentioning
confidence: 99%
“…In addition, some researchers have found that stabilized element formulations can lead to improved performance of iterative solvers, see e.g. [24].…”
Section: Numerical Resultsmentioning
confidence: 99%
“…In here A 22 and b 2 are zero and A 12 -A > 21 . Although the system matrix of (23) is indefinite due to zero diagonal block, recent results indicate that indefiniteness of the problem does not represent a particular difficulty and a recent review of the iterative methods for solving large saddle point problems may be found in [6,39,44]. However, due to the zero diagonal block resulting from the divergence-free constraint, an ILU(k) type preconditioner cannot be used directly for the saddle point problem.…”
Section: Numerical Discretizationmentioning
confidence: 99%
“…This popularity results from factors such as local mass conservation for the lowest order conforming pair (piecewise linear, bilinear or trilinear C 0 velocities and piecewise constant pressures), simple and uniform data structures for the lowest equal order pair (piecewise linear, bilinear or trilinear C 0 velocities and pressures), and algebraic problems with manageable sizes and small bandwidths in three dimensions for both pairs. The latter is of paramount importance in engineering applications where geometry resolution requires very fine meshes and higher order elements can quickly lead to intractable algebraic problems in three space dimensions; see [27] for an example setting.To counteract the lack of LBB stability, low-order pairs are usually supplemented by stabilization or postprocessing procedures that remove spurious pressure modes. Unlike penalty methods (see [16,22,24,25]) for which the goal is to uncouple the pressure and velocity, stabilized methods aim to relax the continuity equation so as to allow application of LBB incompatible spaces.…”
mentioning
confidence: 99%
“…This popularity results from factors such as local mass conservation for the lowest order conforming pair (piecewise linear, bilinear or trilinear C 0 velocities and piecewise constant pressures), simple and uniform data structures for the lowest equal order pair (piecewise linear, bilinear or trilinear C 0 velocities and pressures), and algebraic problems with manageable sizes and small bandwidths in three dimensions for both pairs. The latter is of paramount importance in engineering applications where geometry resolution requires very fine meshes and higher order elements can quickly lead to intractable algebraic problems in three space dimensions; see [27] for an example setting.…”
mentioning
confidence: 99%